Communication Model in Education Development in North Sumatra: A Study on Al Jam'iyatul Washliyah - Tantawi, Iryuha; Arifin , Zainal; Ritonga, Hasnun Jauhari (Faculty of Law, Universitas Pekalongan, 2024)
The study conducted at PW Al Washliyah Sumatera Utara—sourced from the MPW's board—aimed to: 1) elucidate the implementation of organizational communication in the development and cultivation of educational institutions in North Sumatra; 2) identify efforts to ensure the effectiveness of organizational communication; 3) analyze the organizational communication models employed; and 4) describe the challenges or obstacles faced in organizational communication. A qualitative descriptive method was utilized for this research. Informants were purposively selected, totaling eight individuals. Data were gathered through observations, interviews, and document reviews. Subsequently, data were analyzed using Miles and Huberman's data analysis technique, which includes the steps: collection, reduction, display, and conclusion drawing and verification. The research findings are as follows: First, the organizational communication implemented by MPW Al Washliyah Sumatera Utara, which acts as the coordinating and communicative leading sector towards the management of Al Washliyah educational institutions, particularly at the SMTA level, is based on achieving its vision and mission. The acceleration of Al Washliyah educational institutions with predetermined milestone targets was deemed successful, achieving 80 percent of its targeted outcomes. Second, the efforts made by PW Al Washliyah Sumatera Utara to ensure effective organizational communication in the development and cultivation of educational institutions in North Sumatra included striving for formal legality, conducting asset registration, providing socialization/education, and reinforcing development. Third, the organizational communication models applied by PW Al Washliyah in the development and cultivation of educational institutions in North Sumatra are linear, transactional, and interactional/circular/diagonal, with transactional and interactional (circular) models being commonly used. Fourth, the challenges or obstacles frequently encountered include misunderstandings or differing perceptions of communication messages, whether originating from regional leadership or conveyed by heads of schools.